2004
DOI: 10.1093/brain/awh301
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the brain calcium channel CaV2.1 in absence epilepsy and episodic ataxia

Abstract: The molecular basis of idiopathic generalized epilepsy remains poorly understood. Absence epilepsy with 3 Hz spike-wave EEG is one of the most common human epilepsies, and is associated with significant morbidity. Several spontaneously occurring genetic mouse models of absence epilepsy are caused by dysfunction of the P/Q-type voltage-gated calcium channel CaV2.1. Such mice exhibit a primary generalized spike-wave EEG, with frequencies in the range of 5-7 Hz, often associated with ataxia, evidence of cerebella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(121 citation statements)
references
References 46 publications
4
112
0
5
Order By: Relevance
“…A syndrome of absence epilepsy with episodic ataxia similar to that observed in mice has been described in a family with a mutation in the ␣ 1A subunit (Ca v 2.1). 84 In childhood absence epilepsy (CAE), 12 mutations involving CACNA1H (encoding the ␣ 1 subunit Ca v 3.2) have been reported. 85,86 Functional expression studies with several of these mutations have revealed a gain of function.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…A syndrome of absence epilepsy with episodic ataxia similar to that observed in mice has been described in a family with a mutation in the ␣ 1A subunit (Ca v 2.1). 84 In childhood absence epilepsy (CAE), 12 mutations involving CACNA1H (encoding the ␣ 1 subunit Ca v 3.2) have been reported. 85,86 Functional expression studies with several of these mutations have revealed a gain of function.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…Disorders not associated with FHM are episodic ataxia type 2 (Zafeiriou et al 2009, Cuenca-Leon et al 2009, Cricchi et al 2007, Jen et al 2004, 2008, Ophoff et al 1996, progressive ataxia (Yue et al 1997), spinocerebellar ataxia type 6 (Tsou et al , Restituito et al 2000, Ishikawa et al 1999, Zhuchenko et al 1997) and absence (Imbrici et al 2004) and generalized epilepsy (Haan et al 2005, Jouvenceau et al 2001). In addition FHM1 mutations were also found in family members who had only "normal" no-paretic migraine but no FHM.…”
Section: C2 Familial Hemiplegic Migraine Typementioning
confidence: 99%
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%